2021
DOI: 10.1155/2021/6670065
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gastroesophageal Reflux Disease and Elastographic Parameters of Liver Steatosis and Fibrosis: Controlled Attenuation Parameter and Liver Stiffness Measurements

Abstract: Aim. Our aim was to investigate the association among elastographic parameters of liver steatosis and fibrosis, controlled attenuation parameter (CAP) and liver stiffness measurement (LSM), with gastroesophageal reflux disease (GERD). Methods. In this prospective, cross-sectional study, we have evaluated 937 patients with one or more components of the metabolic syndrome who had an esophagogastroduodenoscopy (EGD) due to GERD symptoms. In all patients, a laboratory analysis, an abdominal ultrasound, and FibroSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(77 reference statements)
1
4
0
1
Order By: Relevance
“…To our knowledge, this study is the rst MR analysis to reveal the causation between GERD and NAFLD. We found the overall risk of getting NAFLD is about 71% in people with GERD (OR 1.71; 95% CI 1.40-2.09; P < 0.0001) in MR and meta analysis, by virtue of the GWAS and FinnGen databases [9]. This research is also consistent with Wijarnpreecha, K and Lee, S [12,30].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, this study is the rst MR analysis to reveal the causation between GERD and NAFLD. We found the overall risk of getting NAFLD is about 71% in people with GERD (OR 1.71; 95% CI 1.40-2.09; P < 0.0001) in MR and meta analysis, by virtue of the GWAS and FinnGen databases [9]. This research is also consistent with Wijarnpreecha, K and Lee, S [12,30].…”
Section: Discussionsupporting
confidence: 87%
“…A lot of cohort and observational studies have displayed that people suffering from NAFLD had a higher susceptibility to GERD, and one clinical trial indicated that the risk of re ux esophagitis would increase 16% among people with NAFLD (OR 1.16; 95% CI 1.13-1.20) as compared to those without NAFLD [8,9,10,11]. In addition, a meta-analysis showed that the incidence of NAFLD was higher in people with GERD compared with healthy individuals, with an amalgamated OR of 2.07 (OR 2.07; 95% CI, 1.54-2.79) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the usefulness of CAP is not limited to the liver. The association between CAP-defined NAFLD and coronary artery plaques [ 15 ], increased arterial stiffness [ 30 ], and gastroesophageal reflux disease [ 31 ] has been reported, suggesting the role of CAP as extra-hepatic manifestations in individuals with NAFLD. When we used CAP for the diagnosis of NAFLD, obesity (BMI ≥25), serum triglyceride and the highest tertile of LSM value were significantly associated with NAFLD consistent with previous results [ 25 ], whereas Hp seropositivity was not.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first MR analysis to reveal the causation between GERD and NAFLD. We found the overall risk of getting NAFLD is about 71% in people with GERD (OR 1.71 95% CI 1.40–2.09; P < 0.0001) in MR and meta analysis, by virtue of the GWAS and FinnGen databases 10 . This research is also consistent with Wijarnpreecha and Lee 13 , 33 .…”
Section: Discussionmentioning
confidence: 81%